2020
DOI: 10.1136/bmjopen-2019-031605
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence ofEntamoeba histolyticaat a voluntary counselling and testing centre in Tokyo: a cross-sectional study

Abstract: BackgroundAmebiasis, which is caused byEntamoeba histolytica, is a re-emerging public health issue owing to sexually transmitted infection (STI) in Japan. However, epidemiological data are quite limited.MethodsTo reveal the relative prevalence of sexually transmittedE. histolyticainfection to other STIs, we conducted a cross-sectional study at a voluntary counselling and testing (VCT) centre in Tokyo. Seroprevalence ofE. histolyticawas assessed according to positivity with an ELISA forE. histolytica-specific I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…histolytica infection was performed for HIV-negative MSM individuals. The overall seropositivity (6.7%) was between that found in HIV-positive individuals (21.3%) [ 12 ] and that at a voluntary counselling and testing centre in Tokyo (2.6%) [ 13 ], even though no participants had a previous treatment history of E . histolytica infection at inclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…histolytica infection was performed for HIV-negative MSM individuals. The overall seropositivity (6.7%) was between that found in HIV-positive individuals (21.3%) [ 12 ] and that at a voluntary counselling and testing centre in Tokyo (2.6%) [ 13 ], even though no participants had a previous treatment history of E . histolytica infection at inclusion.…”
Section: Discussionmentioning
confidence: 99%
“…histolytica are asymptomatic [ 11 ]. Indeed, seroprevalence data has shown that asymptomatic infection occurs among sexually active individuals [ 12 , 13 ] who act as a reservoir for sexual transmission. Polymerase chain reaction (PCR) using stool samples is the best method for detecting E .…”
Section: Introductionmentioning
confidence: 99%
“…S. flexneri, S. sonnei, C. jejuni, C. coli , STEC and S. Typhi can be sexually transmitted 1,80–82 The protozoan infection, E. histolytica can cause proctocolitis and is sexually transmissible. 29,32,51,8387 Most cases of sexually transmitted proctocolitis are self-limiting but some may develop severe dysentery, and sepsis. 88…”
Section: Introductionmentioning
confidence: 99%
“…E. histolytica can be sexually transmitted in MSM (particularly in MSM living with HIV), and in heterosexual men and women. 27,29,31,32,51,8387,143146 E. histolytica causes a procto-colitis (and rarely distal ileitis) and can be complicated by liver abscess formation. 26,147,148…”
Section: Introductionmentioning
confidence: 99%
“…Polymerase chain reaction tests were positive for Entamoeba histolytica in stool, and for CMV in colon tissue.Compared with CMV colitis, invasive amoebic colitis is rare, and was detected in only 1.3% of patients with HIV with CD4 + T cell counts <50/mL (Blanshard et al, 1996). Recent studies from Japan have shown the seropositivity rate for E. histolytica to be low among volunteers (2.64%), but much higher among patients with HIV (28.3%) (Yanagawa et al, 2016(Yanagawa et al, , 2020. As gastroenteritis in patients with HIV typically results from multiple pathogens,…”
mentioning
confidence: 99%